Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) International Conference, December 15-17, 2015, Tomsk, Russia [proceedings] - Ardashkin I. B. Igor Borisovich; Martyushev N. V. Nikita Vladimirovich (Les Ulis, EDP Sciences, 2016)
Title screen